2012
DOI: 10.5114/bta.2012.46578
|View full text |Cite
|
Sign up to set email alerts
|

The effect of growth regulators on the regeneration ability of flax ( Linum usitatissimum L.) hypocotyl explants in in vitro culture

Abstract: The aim of the present study is to determine the influence of different concentrations of growth regulators on the hypocotyl explants regeneration abilities of flax cultivars (Linum usitatissimum L.). Plant material used in the study was obtained from two flax cultivars: Modran and Selena. Hypocotyl explants were obtained from 6-dayold seedlings and were subsequently placed on basal MS (Murashige and Skoog 1962) medium and MS medium supplemented with 6-benzylaminopurine (BAP) or naftalene acetic acid (NAA). Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
15
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 18 publications
6
15
0
4
Order By: Relevance
“…It was shown that light green compact calli and shoot proliferation were obtained from hypocotyl explants on medium MS-BN containing 1 mg/l BAP and 0.05 mg/l NAA. Similar studies were conducted in the works [55,66,[74][75][76][77][78]. The inducing effect of various concentrations of growth regulators NAA, BAP, TDZ and 2iP added into basal MS medium on the formation of callus, shoot and root from hypocotyl explants of Linum usitatissimum L. was studied [55].…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…It was shown that light green compact calli and shoot proliferation were obtained from hypocotyl explants on medium MS-BN containing 1 mg/l BAP and 0.05 mg/l NAA. Similar studies were conducted in the works [55,66,[74][75][76][77][78]. The inducing effect of various concentrations of growth regulators NAA, BAP, TDZ and 2iP added into basal MS medium on the formation of callus, shoot and root from hypocotyl explants of Linum usitatissimum L. was studied [55].…”
Section: Discussionmentioning
confidence: 69%
“…Data of our previous researches and numerous data of other authors witness that regeneration ability of flax (Linum usitatissimum L.) is under the influence of various types of growth regulators and their different concentrations in the culture media as well as origin of the plant explants [55,[62][63][64][65][66][75][76][77][78].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations